Exploring the Interaction of Personality, Strategy, and Learning Environment in Achieving Success in Learning Arabic Grammar - Moh. Buny Andaru Bahy; Mohammad Samsul Ulum; Halimi Zuhdy; Aulia Rahman; Mirwan Akhmad Taufiq; Abdul Wahab Naf'an (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study explored the interplay of personality, learning strategies, and learning environments in achieving success in Arabic grammar learning. A narrative inquiry approach was employed, with participants purposively selected based on their outstanding achievements in Arabic grammar competitions. Data were collected through in-depth interviews, and participants’ experiences were reconstructed and interpreted for analysis. The findings indicated that, in addition to effective instructional management and well-structured curriculum design, the integration of constructive personality traits, strategic learning approaches, and supportive learning environments significantly contributed to learners’ success in mastering Arabic grammar.